POTENSI OBJEK WISATA PANTAI POHON SERIBU SASAK KECAMATAN SASAK RANAH PASISIA - putra, Arion Aswandi (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to analyze (1) site potential (2) management of tourist objects (3) role and function of pokdarwis in the Seribu Tree Beach tourist area. This research is a descriptive study with a qualitative approach which was carried out in October 2022 at the Seribu Tree Beach, Nagari Sasak, Sasak Ranah Pasisia District, West Pasaman Regency. Data collected through observation, interviews, documentation. For the validity of the data, repeated interviews were carried out and conclusions were drawn to produce valid data. This study found (1) The potential site on the Thousand Trees beach tourist attraction is in the form of a large beach area so that tourists can play freely, vegetation in the form of pine trees which provide coolness for tourists to visit. relaxation, currents and wind speed that provide comfort and a sense of security for tourists, a sloping beach slope so that tourists can play and also the availability of a breakwater that provides benefits as an abrasion prevention and as a photo spot for tourists (2) management of the Thousand Trees beach attraction during the day usually done by pokdarwis and during big days such as holidays, events or beach parties will be held through collaboration between community youth and pokdarwis (3) Pokdarwis on the Thousand Trees beach tourist object function as supervisors and at the same time manage tourism objects, which pokdarwis in i was fostered by the West Pasaman Tourism Office.